Acute respiratory complication presenting at birth due to an intra‐oral teratoma arising from the tonsil. (3rd March 2014) - Gomes, S.; Rashid, M.; Acharya, V.
Abstract: Oral teratomas are rare congenital tumours. They can result in rapid asphyxia following birth if undetected prenatally. Antenatal ultrasound diagnosis allows for careful and early evaluation, thereby leading to timely intervention. This report highlights a male infant delivered prematurely but spontaneously with an unremarkable prenatal course and normal antenatal scans who was then found to have an intraoral teratoma requiring intubation, diagnosed using MRI scans. Upon ENT surgical intervention for removal, it was found to arise from the tonsil. This report will focus on acute management and surgical intervention in a prenatally undiagnosed case.